Combined-stimulus control as a function of the response rate controlled by the absence of the single stimuli - Wiltz, Robert A. (1972)
Rat's bar-press responses were maintained at moderate rates during separate presentations of light and tone by separate but concurrent variable-interval schedules of food and shock presentation. The relative response rate maintained during light-out-no-tone was alternated in four successive phases: in Phases 1 and 3 responding was maintained at a higher rate than that during light and tone alone by a variable-interval food schedule, while in Phases 2 and 4 responding was reduced to a lower rate by a differential-reinforcement-of-other-behavior food schedule. In test presentations of light, tone and a light-plus-tone combination, administered at the end of each phase, the proportion of responses emitted during light-plus-tone was an inverse function of the relative response rate controlled by light-out-no-tone, indicating that the relative training response rate controlled by the absence of the single stimuli determined the control exerted by the combined stimuli. Different relative response rates maintained in training may also be partly responsible for previously observed differences in the form of generalization gradients following the establishment of multi-stimulus control.